Dynamic Perturbations of the T-Cell Receptor Repertoire in Chronic HIV Infection and following Antiretroviral Therapy - Heather, James M.; Best, Katharine; Oakes, Theres; Gray, Eleanor R.; Roe, Jennifer K.; Thomas, Niclas; Friedman, Nir; Noursadeghi, Mahdad; Chain, Benjamin (Frontiers in Immunology, 2016)
HIV infection profoundly affects many parameters of the immune system and ultimately leads to AIDS, yet which factors are most important for determining resistance, pathology and response to antiretroviral treatment – and how best to monitor them – remain unclear. We develop a quantitative high throughput sequencing pipeline to characterise the TCR repertoires of HIV-infected individuals before and after antiretroviral therapy, working from small, unfractionated samples of peripheral blood. This reveals the TCR repertoires of HIV+ individuals to be highly perturbed, with considerably reduced diversity as a small proportion of sequences are highly over-represented. HIV also causes specific qualitative changes to the repertoire including an altered distribution of V gene usage, depletion of public TCR sequences and disruption of TCR networks. Short term anti-retroviral therapy has little impact on most of the global damage to repertoire structure, but is accompanied by rapid changes in the abundance of many individual TCR sequences, decreases in abundance of the most common sequences, and decreases in the majority of HIV-associated CDR3 sequences. Thus high-throughput repertoire sequencing of small blood samples that are easy to take, store and process can shed light on various aspects of the T-cell immune compartment and stands to offer insights into patient stratification and immune reconstitution.